2011
DOI: 10.1038/ejcn.2011.108
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic study of orlistat 60 mg on abdominal obesity

Abstract: Background and Aims: It is well established combining a reduced calorie, low fat diet with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Recently, an open label, 3 month study using orlistat 60 mg was conducted to examine changes in fat distribution. The authors reported decreases in VAT and body weight at 12 weeks which were similar to the current results (14). Using proton magnetic resonance spectroscopy ( 1 H‐MRS), a 43% reduction in intra‐hepatocellular lipids was observed; in the current study, there was a 27% reduction in liver fat, based on CT. Hepatic measurements obtained by CT and liver biopsy correlate well with intra‐hepatocellular lipids as measured by 1 H‐MRS (30,31).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Recently, an open label, 3 month study using orlistat 60 mg was conducted to examine changes in fat distribution. The authors reported decreases in VAT and body weight at 12 weeks which were similar to the current results (14). Using proton magnetic resonance spectroscopy ( 1 H‐MRS), a 43% reduction in intra‐hepatocellular lipids was observed; in the current study, there was a 27% reduction in liver fat, based on CT. Hepatic measurements obtained by CT and liver biopsy correlate well with intra‐hepatocellular lipids as measured by 1 H‐MRS (30,31).…”
Section: Discussionsupporting
confidence: 91%
“…The 60 mg dose has been shown to have approx 85% the efficacy of the 120 mg dose (11,12). Some preliminary studies have examined the effect of orlistat 120 mg capsules on changes in body composition (13,14,15). In particular, Tiikkainen et al (13) showed that the 120 mg dose of orlistat was effective in reducing visceral fat greater than diet alone, despite similar weight loss.…”
Section: Introductionmentioning
confidence: 99%
“…51,55 The remaining 12 studies (2 studies were single-group pre-post designs, 1 study had a more active comparison group, and 9 studies reported outcomes at < 12 mo) were only included in analyses of adverse events. 24,29,57,63,[75][76][77][78][79][80][81]83 High within-group heterogeneity was common; however, the direction of treatment effect was consistent across most studies, and the confidence intervals overlapped. This statistical heterogeneity is likely due to small versus large treatment effects observed across studies.…”
Section: Resultsmentioning
confidence: 99%
“…Improvements in blood pressure, waist circumference, total cholesterol and LDL cholesterol were also greater with orlistat than with placebo . Even at the over‐the‐counter dose of 60 mg three times daily (brand name Alli®), improvements in body composition, lipid profiles and blood pressure may be observed . Orlistat has well‐known gastrointestinal adverse events, including faecal leakage .…”
Section: Current Status Of Pharmacological Weight Management In the Umentioning
confidence: 99%